1989
DOI: 10.1016/0014-5793(89)81387-0
|View full text |Cite
|
Sign up to set email alerts
|

Neuroactive metabolises of L‐tryptophan, serotonin and quinolinic acid, in striatal extracellular fluid effect of tryptophan loading

Abstract: Extracellular fluid levels of the neurotoxin quinolinic acid in the corpus striatum of rats, measured by in vivo microdialysis, were increased in a dose-dependent manner following the intraperitoneal administration of tryptophan. The lowest dose of tryptophan (12.5 mg/kg), equivalent to about 5% of the normal daily intake, increased peak quinolinic acid levels nearly 3-fold. At higher doses of tryptophan (up to 250 mg/kg), concentrations of quinolinic acid increased over 200-fold and exceeded potentially neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…The concentrations of extracellular tryptophan, kynurenine and QUIN in naïve rats were in line with studies using various detection methods, including ECNI [31,32,40,41]. Interestingly, ambient kynurenine levels in brain microdialysates from normal rats (~500 nM when corrected for the ~20% recovery from the dialysis probe) were only slightly lower than kynurenine concentrations in rat brain tissue and serum, respectively [42,43].…”
Section: Discussionsupporting
confidence: 76%
“…The concentrations of extracellular tryptophan, kynurenine and QUIN in naïve rats were in line with studies using various detection methods, including ECNI [31,32,40,41]. Interestingly, ambient kynurenine levels in brain microdialysates from normal rats (~500 nM when corrected for the ~20% recovery from the dialysis probe) were only slightly lower than kynurenine concentrations in rat brain tissue and serum, respectively [42,43].…”
Section: Discussionsupporting
confidence: 76%
“…The concentrations measured in the human epileptic brain (∼10 μM) were in the range of neurotoxic and seizure promoting levels (During et al, 1989). Since QA levels in the brain are topographically overlapping with abnormal epileptiform activity, we propose a scenario where multiple drug resistance not only impedes CBZ access to the brain, but also leads to exacerbation of seizures by a powerful metabolic process.…”
Section: Discussionmentioning
confidence: 99%
“…One Kyn metabolite, quinolinic acid (QA), is a selective NMDA receptor agonist (reviewed in Freese et al (1990)), and a monoamine oxidase-B (MAO-B) inhibitor (Naoi et al 1987). A peripherally-administered dose of Trp which less than doubled extracellular brain 5-HT in rats increased the brain QA concentration 80-fold (During et al 1989), and QA has been shown to have stimulant (Lapin 1978) and anxiogenic (Lapin 1996) properties in animals. These data collectively suggest a potential for a large Trp bolus to alter behavior by: 1) heightened NMDA receptor activation, and 2) increased norepinephrine neurotransmission by inhibiting catecholamine elimination by MAO-B.…”
Section: Discussionmentioning
confidence: 99%